Catalytic Oxidative Coupling Cyclization for Construction of Benzofuroindolenines under Mild Reaction Conditions. Issue 3 (5th December 2018) - Lin, Yuqi; Ye, Jinxiang; Zhang, Wenting; Gao, Yu; Chen, Haijun
Abstract: We describe iron‐catalyzed oxidative coupling cyclization of tetrahydrocarbazoles or THβCs or THγCs to form benzofuroindolenines as fused polycyclic indoles. This mild, efficient and simple approach afforded a library of more than 52 complex compounds across a range of substrate classes with good to excellent yields. Abstract :